Acid deposition induced base cation loss and different responses of soils and sediments in Taihu Lake watershed, China. (July 2019) - Dan, Dai; Tao, Yu; Yixiang, Deng; Fuhong, Sun; Jian, Zhao; Chengda, He
Abstract: Acid deposition and algae blooms have resulted in great changes in the water chemistry of Taihu Lake; however, there have been few calculated results to describe these processes. Here we used a mass balance model to estimate base cation losses and evaluate the model applicability in this intensively human-impacted watershed based on a long-term database (1985–2015). The results showed that carbonate weathering induced Ca 2+ and Mg 2+ losses in the watershed were responsible for the increased ion net reaction (INR) of Ca 2+ and Mg 2+ in the lake. While the increase of K + and Na + were not appropriate to provide independents check on the mass balance model because they generally entered the lake as human discharges, not reflecting change of the geochemical process in the watershed as the watershed dominant bedrock is carbonate but not silicate. Acid deposition in Taihu region caused decrease in pH, lime potential, and different Ca, Mg species of surface soils. Our field measurements of sediments in the two lake parts showed that the sediment lime potential was significantly higher in the algae dominated lake area than in the hydrophyte-dominated area due to the in-lake alkalinization by algae blooms, indicating that algae blooms played a significant role in the acidification resistance. Meanwhile, the measured lime potential of the watershed soils was lower than that of the sediment, implying a potential risk of acidification in the watershed. This research helps understand the accelerated interactions between human activities and natural geochemical processes and accelerated water chemistry change at the watershed level. Graphical abstract: Image 1 Highlights: Mass balance model reveals increased base cation losses from watershed to Taihu Lake in the past decades. Human-induced carbonate weathering has accelerated and altered the natural geochemical balance. Concentrations of Ca and Mg species are differentiated in soils and sediments due to impacts of acid deposition. Watershed soils have become more sensitive to acid deposition than lake sediments.